Meningococcal B vaccine antigen FHbp variants among disease-causing Neisseria meningitidis B isolates, Italy, 2014–2017 - Carannante, Anna (PLoS One, 2020)
BACKGROUND: Typing of Neisseria meningitidis isolates is crucial for the surveillance of invasive meningococcal disease (IMD). We performed a molecular epidemiology study of N. meningitidis serogroup B (MenB) causing IMD in Italy between 2014 and 2017 to describe circulating strains belonging to this serogroup, with particular regards to the two factor H-binding protein (FHbp) subfamilies present in the bivalent MenB vaccine. MATERIALS AND METHODS: A total of 109 culture positive and 46 culture negative MenB samples were collected within the National Surveillance System (NSS) of IMD in Italy and molecularly analyzed by conventional methods. RESULTS: Overall, 71 MenB samples showed the FHbp subfamily A and 83 the subfamily B. The subfamily variants were differently distributed by age. The most frequent variants, A05 and B231, were associated with cc213 and cc162, respectively. All MenB with the FHbp A05 variant displayed the PorA P1.22,14 and 85.7% of them the FetA F5-5. The majority of MenB with the FHbp B231 variant showed the PorA P1.22,14 (65.4%) and 84.6%, the FetA F3-6. CONCLUSION: MenB circulating in Italy were characterized by a remarkable association between clonal complex and FHbp variants, although a high degree of genetic diversity observed over time. A dynamic trend in clonal complexes distribution within MenB was detected. Our results stress the importance of continued meningococcal molecular surveillance to evaluate the potential vaccine coverage of the available MenB vaccines.